Phytochemical analysis of Holothuria leucospilota, a sea cucumber from Persian Gulf - Mohammad Reza Shushizadeh; Pardis Mohammadi pour; Mohaddeseh Mahdieh; Afsaneh Yegdaneh (Wolters Kluwer Medknow Publications, 2019)
Sea cucumbers are widely consumed in traditional medicine and food. These animals have a considerable secondary metabolite and also several potential biological activities. This study investigated the phytochemical and cytotoxic evaluation of Holothuria leucospilota (H. leucospilota), a sea cucumber from Persian Gulf. The saponin composition of H. leucospilota was studied by different partitioning and chromatography methods such as thin layer chromatography (TLC), medium pressure liquid chromatography (MPLC) and high performance LC (HPLC). The marine sea cucumber Holostane-type triterpenoids (1-3) were characterized by physical and spectroscopic examination (1 and 2 dimensional neuclear magnetic resonance and mass experiments) with data analysis. The structure of compounds 1-3 identified as echinoside A, holothurine A, and 24-dehydroechinoside A, showed moderate cytotoxic activity with IC50 values of 1.9 ± 0.07, 6.8 ± 0.23, and 2.57 ± 0.18 μ/mL against HeLa and 10.4 ± 0.32, 8.9 ± 0.24, and 4.4 ± 0.13 on HUVEC cell line, respectively. In conclusion, the holostane-type triterpenoids showed moderate cytotoxic activity against HeLa cell line and have a prosperous future to be introduced as a lead structure.